PENGARUH PERAN GANDA, FLEKSIBILITAS JAM KERJA DAN GAJI TERHADAP KESEJAHTERAAN PERAWAT PEREMPUAN PADA RUMAH SAKIT PANTI WILASA CITARUM SEMARANG - Kurnia Dwi; Ari Pradhanawati (Jurnal Ilmu Administrasi Bisnis, 2018)
Along with the development of the era, Indonesia became one of the countries also affected by globalization, where the Indonesian women workforce increased from year to year. One of them is at Panti Wilasa Citarum Hospital which has a female nurse greater than male nurse. Women working for double roles, and working hours and salary cooperation to fulfill their welfare.The purpose of this research is to know the influence of double role, working hours, and salary to the welfare of female nurses at Panti Wilasa Citarum Semarang Hospital. This type of research is explanatory research, with sampling technique, sample census where all population is made responder. And the sample is 122 resondents. This research technique is quantitative analysis, reliability test, simple and multiple regression test, which is test of determination, significance test (t test and f), classic aesthetic test. The results of this study indicate a strong relationship between multiple roles, work diving work and welfare salary in which the queen is 0.4686. The three independent variables have a positive relationship. This is proved by the result of double role regression 0.441, following working hours 0.355, and salary of 0.633. The value of F arithmetic (34,991)> from F table (2.13).Double roles, flexibility working hours and salaries simultaneously affect welfare positively and significantly. The effect is positive, the better the double role, the flexibility of working hours, and the salary will be better the welfare of female nurses, and vice versa. Based on the results of the study, the author of the Hospital theory to better support the welfare of women by raising salaries, giving sick child special leave and giving pension